Abundance of native rhizobia nodulating cowpea in major production areas of Ethiopia as influenced by cropping history and soil properties. Issue 1 (1st January 2021) - Kebede, Erana; Amsalu, Berhanu; Argaw, Anteneh; Tamiru, Solomon
ABSTRACT: Enumeration of the native rhizobia population is important to determine the abundance of rhizobia in the soil and the achievement of inoculation. In Ethiopia, limited information is available on the population abundance of cowpea nodulating rhizobia. This study aimed to evaluate the population abundance of rhizobia nodulating cowpea and their relation with cropping history and soil properties in cowpea producing areas of Ethiopia. The abundance of rhizobia existing in the soils was assessed by the most probable number technique. The study revealed that the population abundance of rhizobia nodulating cowpea is high, ranging from 3.1 × 10 4 to 1.0 × 10 7 rhizobia cells g −1 of soil, and the population varied at each location. Besides, there was no statistically significant correlation between soil physicochemical properties and the rhizobial population. All the investigated soils had been cropped with cowpea in monoculture (sole cowpea), intercropping (mostly with sorghum and maize) and crop rotation for many years. Thus, the higher rhizobia population observed in this study is associated with the season factor and cropping history of the areas. In general, the soils of cowpea production areas in Ethiopia harbor adequate levels of rhizobia capable of nodulating cowpea, which are passable to provide satisfactory nitrogen fixation and nodulation.